1 Peter - Horrell, David G. 1963- (New York, NY [u.a.] T & T Clark, 2008)
Rescuing 1 Peter -- What kind of text is 1 Peter? -- Traditions in 1 Peter -- The situation, indentity, and suffering of the addressees of 1 Peter -- Jewish scriptures and Christian identity -- Becoming Christian in a hostile world -- Assessing 1 Peter : an ambivalent legacy?
Includes bibliographical references and indexes
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc